ZmACY-1 Antagonistically Regulates Growth and Stress Responses in Nicotiana benthamiana - Chen, Dongbin; Li, Junhua; Jiao, Fuchao; Wang, Qianqian; Li, Jun; Pei, Yuhe; Zhao, Meiai; Song, Xiyun; Guo, Xinmei (Frontiers in Plant Science, 2021)
Aminoacylase-1 (ACY-1) is a zinc-binding enzyme which is important in urea cycling, ammonia scavenging and oxidative stress responses in animals. ACY-1 has been reported to play a role in resistance to pathogen infection in the model plant Nicotiana benthamiana. However, little is known about its function in plant growth and abiotic stress responses. In this study, we cloned and analyzed expression patterns of ZmACY-1 in Zea mays under different conditions. We also functionally characterized ZmACY-1 in N. benthamiana. We found that ZmACY-1 is expressed specifically in mature shoots compared to other tissues. ZmACY-1 can be repressed by salt, drought, jasmonic acid and salicylic acid, but is induced by abscisic acid and ethylene, indicating a potential role in stress responses and plant growth. Overexpression of ZmACY-1 in N. benthamiana promoted the growth rate, by promoting the growth-related genes, including NbEXPA1 and NbEIN2. At the same time, overexpression of ZmACY-1 in N. benthamiana reduced tolerance to drought and salt stress. Under drought and salt stress, the activity of protective enzymes such as Peroxidase (POD), Superoxide dismutase (SOD) and Catalase from micrococcus lysodeikticus (CAT) was lower; while the content of malondialdehyde (MDA) and relative electrolytic leakage was higher in ZmACY-1 overexpression lines than that in wildtype lines. Our results indicate that ZmACY-1 plays an important role in the balance of plant growth and defense and can be used to assist plant breeding in abiotic stress conditions.